iPhone for Work Increasing Productivity for Busy Professionals - Faas, Ryan (Apress : Imprint: Apress, 2010)
The iPhone is cool, and the iPhone is fun, but the iPhone also means serious business. For those of you who bought your iPhones to help get your lives organized and free yourselves from the ball and chain of desktop computing, iPhone at Work: Productivity for Professionals is the book to show you how. There are plenty of general-purpose iPhone guides, but iPhone at Work: Productivity for Professionals shows you how to complete all the traditional smartphone tasks, like to-do lists, calendars, and e-mail, and become much more efficient and productive at work. You'll learn mechanisms for developing effective workflows specific to the features of the iPhone and also efficient strategies for dealing with the specialized aspects of business and professional lifestyles. From the introduction and throughout the book, author Ryan Faas targets professional users of the iPhone. You'll tour the built-in applications and configuration options, always with work and productivity in mind, and discover all of the enterprise features of the iPhone, learning how to configure and use each one. Then discover the App Store: source of all third-party software. There's something a bit daunting about the dominance of games and frivolous apps on the best-seller lists, but there are serious business and vertical applications also available, and you'll learn about some of the best and how to take advantage of this wealth of add-on and very professional functionality. And for those administrators with the special job of deploying lots of new iPhones across the enterprise, this book concludes with two appendixes that provide information and resources for companies. The first is intended for organizations looking to perform larger-scale iPhone or iPod touch deployments complete with device management. The second is geared for those companies that wish to develop an iPhone platform-oriented infrastructure through the use of customized in-house applications and iPhone/iPod touch-specific web services.